ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION :AN ENGLISH COURSE DESIGN AT A STATE UNIVERSITY - Petrus, Ismail (2012)
There is some controversy on the issue of the type of English course for undergraduate students whether it should be of general purposes or specific purposes. This dissertation attempts to address this issue. The dissertation first looks into the present English course, and then conducts a needs analysis of the students and faculty's management, and finally proposes a course design on the basis of the needs analysis. The site of the research is the Faculty of Teacher Training and Education of a state university in South Sumatra. The participants include 378 second-semester students of 7 study programs, 10 language instructors, 7 heads of study programs, 2 heads of departments, 2 faculty's heads, and the head of the university's language institute. The data were collected through (a) a questionnaire given to 378 students in 15 classes, (b) interviews with the instructors, the heads of departments/study programs, the faculty's heads, the language institute head, (c) observations in the classroom, and (d) review of the documents. In general, the data were analyzed in three phases: description, analysis, and interpretation (Wolcott, 1994). In the process within the phases, the data were described, analyzed, and interpreted quantitatively by using tables and graphs, and qualitatively in descriptive narrative form. The findings of the research give a portrait of the present English course (in terms of such aspects as institutional goals, class management, instructional materials, instructors, teaching methodology, and evaluation) and provide the information on the student profile, the target needs and learning needs, which becomes the basis for designing a new English course. Regarding the present English course, the findings show: (1) no needs analysis was conducted prior to designing the course, (2) since no needs analysis was conducted, no collaboration was among the stakeholders in designing the course, (3) the classes were relatively big with theatre-seating, (4) the course reviewed what had been taught in high schools, and (5) no course evaluation was conducted to seek the effectiveness, efficiency, and cceptability of the course. On the basis of the findings, it can be concluded that the present English course was General English. Concerning the needs analysis, the results reveal that the students need to develop their reading skill in order to be able to comprehend reading texts, to develop their speaking skill in order to be able to give an oral presentation, and to understand grammatical and vocabulary items in order to support the reading skill. Following the process of Nation & Macalister's (2010) model of curriculum design, a new English course design is produced as a proposal. The curriculum design process consists of environmental analysis, needs analysis, principles of language teaching and learning, goals and objectives, content and sequencing, format and presentation, monitoring and assessment, and evaluation. The proposed course design therefore includes such aspects as the course rationale, goals and objectives, the skills syllabus, the materials, the learning activities, the monitoring and assessment, and the course evaluation. The prospective course can be considered as an EGAP (English for General Academic Purposes) course because the course has a skills syllabus, which stresses on developing the reading micro-skills of the students in the context of education.